Un’autoanalisi spietata: Il Conoscente di Umberto Fiori - Bistolfi, Chiara (L'ospite ingrato, 2022)
This paper examines Umberto Fiori’s latest work, Il Conoscente, released by Marcos y Marcos in 2019. Defined by the author himself as a “falsely autobiographical story in verse”, the work is the result of a self-analysis that the subject leads on himself, on his idea of poetry, on his own activity as a poet and on different aspects of his life. Starting from the studies on the lyric carried out by Damiano Frasca (in particular in Posture dell’io. Luzi, Sereni, Giudici, Caproni, Rosselli, Pisa, Felici, 2014) which identifies certain tendencies of the subject to narrative forms and dialogue as phenomena functional to a strengthening of the inner monological discourse, we tried to identify the textual places that involve the identity aspect, focusing attention on three levels of analysis: the “I” in the first person, the “Umberto Fiori” as subject and protagonist, the subject as a poet and bearer of an idea of poetry and, finally, the “we”, to be understood as a political and community perspective.